Biomechanics of Immediate Postextraction Implant Osseointegration. (August 2018) - Yuan, X.; Pei, X.; Zhao, Y.; Li, Z.; Chen, C.H.; Tulu, U.S.; Liu, B.; Van Brunt, L.A.; Brunski, J.B.; Helms, J.A.
The aim of this study was to gain insights into the biology and mechanics of immediate postextraction implant osseointegration. To mimic clinical practice, murine first molar extraction was followed by osteotomy site preparation, specifically in the palatal root socket. The osteotomy was positioned such that it removed periodontal ligament (PDL) only on the palatal aspect of the socket, leaving the buccal aspect undisturbed. This strategy created 2 distinct peri-implant environments: on the palatal aspect, the implant was in direct contact with bone, while on the buccal aspect, a PDL-filled gap existed between the implant and bone. Finite element modeling showed high strains on the palatal aspect, where bone was compressed by the implant. Osteocyte death and bone resorption predominated on the palatal aspect, leading to the loss of peri-implant bone. On the buccal aspect, where finite element modeling revealed low strains, there was minimal osteocyte death and robust peri-implant bone formation. Initially, the buccal aspect was filled with PDL remnants, which we found directly provided Wnt-responsive cells that were responsible for new bone formation and osseointegration. On the palatal aspect, which was devoid of PDL and Wnt-responsive cells, adding exogenous liposomal WNT3A created an osteogenic environment for rapid peri-implant bone formation. Thus, we conclude that low strain and high Wnt signaling favor osseointegration of immediate postextraction implants. The PDL harbors Wnt-responsive cells that are inherently osteogenic, and if the PDL tissue is healthy, it is reasonable to preserve this tissue during immediate implant placement.